Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006757.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for cataracts in people with age-related macular degeneration

Abstract: Background Cataract and age-related macular degeneration (AMD) are significant causes of decreased vision in the elderly that often occur simultaneously. Although cataract surgery is an effective treatment for cataract-induced visual loss, some clinicians suspect that such an intervention may increase the risk of progression of underlying AMD and thus have deleterious effects on vision. Objectives The objective of this review was to evaluate the effectiveness and safety of cataract surgery in eyes with AMD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The effect of cataract surgery on progression of AMD was previously evaluated by a Cochrane review (Casparis et al. ). That review only included data from published randomized controlled trials, resulting in a recommendation based on one included study.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of cataract surgery on progression of AMD was previously evaluated by a Cochrane review (Casparis et al. ). That review only included data from published randomized controlled trials, resulting in a recommendation based on one included study.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest evidence supporting development of advanced AMD in the postoperative period was provided by large population-based epidemiologic studies [ 4 7 ]. However, a cochrane review of the literature was unable to determine whether cataract surgery was beneficial or harmful in patients with AMD [ 18 ]. More recently, data from the Age-Related Eye Disease Study (AREDS) concluded that cataract surgery is safe in the setting of dry AMD and did not accelerate progression to advanced sight threatening forms of AMD [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written about the risks and benefits of cataract surgery in patients with AMD (Casparis et al 2017). In particular, there is evidence to show that cataract surgery may be associated with increased choroidal neovascular membrane activity in exudative AMD (Daien et al 2018).…”
Section: Discussionmentioning
confidence: 99%